Production and characterization of high-affinity human monoclonal antibodies to human immunodeficiency virus type 1 envelope glycoproteins in a mouse model expressing human immunoglobulins. - Sheppard, N; Davies, S; Jeffs, SA; Vieira, S; Sattentau, Q (2007)
Human (Hu) monoclonal antibodies (MAbs) against the human immunodeficiency virus type 1 (HIV-1) envelope glycoproteins (Env) are useful tools in the structural and functional analysis of Env, are under development both as potential prophylaxis and as therapy for established HIV-1 infection, and have crucial roles in guiding the design of preventative vaccines. Despite representing more than 50% of infections globally, no MAbs have been generated in any species against C clade HIV-1 Env. To generate HuMAbs to a novel Chinese C clade Env vaccine candidate (primary isolate strain HIV-1(97CN54)), we used BAB5 mice that express a human immunoglobulin (Ig) M antibody repertoire in place of endogenous murine immunoglobulins. When immunized with HIV-1(97CN54) Env, these mice developed antigen-specific IgM antibodies. Hybridoma fusions using splenocytes from these mice enabled the isolation of two Env-specific IgM HuMAbs: N3C5 and N03B11. N3C5 bound to HIV-1 Env from clades A and C, whereas N03B11 bound two geographically distant clade C isolates but not Env from other clades. These HuMAbs bind conformational epitopes within the immunodominant region of the gp41 ectodomain. N3C5 weakly neutralized the autologous isolate in the absence of complement and weakly enhanced infection in the presence of complement. N03B11 has no effect on infectivity in either the presence or the absence of complement. These novel HuMAbs are useful reagents for the study of HIV-1 Env relevant to the global pandemic, and mice producing human immunoglobulin present a tool for the production of such antibodies.